Pemaknaan “Duri dalam Daging” di 2 Korintus 12:7 sebagai Penguatan dalam Menghadapi Penderitaan Orang Percaya - Efesus Suratman (Sekolah Tinggi Alkitab Jember, 2023)
Suffering knows no boundaries; everyone can experience various hardships, including believers. The presence of suffering often leads believers to forsake God, posing a problem addressed in this research. The method used in this study is literature research, where the first thing explained is the understanding of suffering for believers, followed by the search for the meaning of